PENGARUH PENGGUNAAN MEDIA INTERNET TERHADAP MOTIVASI BELAJAR SISWA PROGRAM KEAHLIAN AKUNTANSI DI SMK NEGERI 1 MAKASSAR - Sahade, Sahade; Rijal, H. Abd.; Nur, Anugrah Atunnisa (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This study aims to determine the magnitude of the influence of the use of internet media on students' motivation to study accounting skills programs at SMK Negeri 1 Makassar. The variables in this study are the use of internet media as an independent variable (X) and students' learning motivation as the dependent variable (Y). The population in this study were all students of the accounting expertise program at SMK Negeri 1 Makassar, totalling 418 students in the 2020/2021 academic year. The sampling technique used is proportionate stratified random sampling with a sample of 80 students taken randomly and proportionally. Data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive percentage analysis, instrument test and hypothesis testing. The instrument test consists of a validity test and a reliability test. Hypothesis testing consists of simple linear regression analysis, t-test, and coefficient of determination test. The results of the data analysis carried out, based on 3 (three) indicators measured the variable use of internet media included in the sufficient category, while for student learning motivation with 8 (eight) indicators measured were also in the fairly good category. The results of hypothesis testing using the Simple Linear Regression Test obtained the equation model Y = 24,352 + 0.314X, this means that if the use of internet media is zero, then the student motivation variable for the accounting skills program at SMK Negeri 1 Makassar is 24,352 units. From the results of the analysis of the coefficient of determination (r2), the value of r2 = 11.8%, which means that the influence of internet media use on learning motivation is 11.8% while the remaining 88.2% is influenced by other factors. The product-moment correlation results obtained an R-value of 0.343 or 34.3%, this shows the relationship between the variable (X) of internet media use and the variable (Y) of students' learning motivation has a low relationship (scale 0.200-0.399). Meanwhile, the results of the t-test analysis obtained a significant value of 0.002 <0.05, which means that the use of internet media has a positive and significant effect on students' learning motivation, thus the hypothesis is accepted. The implementation of this application shows that the learning media in this case the internet makes students as millennial generations able to learn independently, where the internet as a learning medium has become a basic need that cannot be avoided so that it is very interesting to motivate students to want to study seriously with the material/ the subject given. This proves that the internet can be used as a learning medium, not just using it as social media but as an appropriate learning medium in increasing students' learning motivation.